CASE REPORT OF ADULT-ONSET CHARCOT MARIE TOOTH TYPE X - Suherlim, Richard; Laksmidewi, Anak Agung Ayu Putri; NKA, Sudiarini (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Charcot-Marie-Tooth (CMT) or Hereditary Motor and Sensory Neuropathy (HMSN) is the most common hereditary peripheral nerve disease with progressive chronic weakness, muscle atrophy, and sensory disturbances. There are several types and subtypes of CMT with their respective clinical manifestations. In this article, we reported a patient with of CMT type X. A 43-year-old male patient was referred to a neurology clinic with weakness in both limbs for 2 years, accompanied by tingling and sensory disturbance in both hands and feet. There are several of his family members who had similar complaints. Lumbosacral magnetic resonance imaging (MRI) examination revealed mild nucleus pulposus herniation. Electroneuromyography (ENMG) examination revealed demyelinating sensory motor polyneuropathy. Histopathological examination of nerve biopsy showed demyelination of the sural nerve. It is hard to make a diagnosis of CMT, because it requires high suspicion from clinicians once encounter a suspected case and also need to supported by sophisticated equipment such as electrophysiological examinations, nerve biopsy examinations, and genetic examinations. It is vital for clinicians for being able to diagnose CMT correctly and provide treatment as soon as possible in order to maintain the patients’ quality of life.